2021
DOI: 10.1021/acsanm.1c01279
|View full text |Cite
|
Sign up to set email alerts
|

Black Phosphorus Nanosheets Integrated with Gold Nanoparticles and Polypyrrole for Synergistic Sonodynamic and Photothermal Cancer Therapy

Abstract: Intractable cancer has threatened human health all the time. Emerging sonodynamic and photothermal therapy based on biocompatible black phosphorus (BP) nanomaterials have become an attractive strategy due to the satisfactory synergistic effect, low side effect, and good biocompatibility. However, sonodynamic therapy of pure black phosphorus nanosheets (BPS) is limited for fast electron recombination owing to its special band gap. To solve this challenge, the modified nanocomposites (NCs) integrating gold nanop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…For example, theranostic platforms integrating collaborative chemotherapy, PTT, radiotherapy, and imaging diagnosis have been designed and verified to be useful for imaging diagnosis and enhanced tumor treatment. [158,159] However, the future clinical applications of 2D NMs still face great challenges. The major barrier is their long-term safety, especially for substances that are not biodegradable in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, theranostic platforms integrating collaborative chemotherapy, PTT, radiotherapy, and imaging diagnosis have been designed and verified to be useful for imaging diagnosis and enhanced tumor treatment. [158,159] However, the future clinical applications of 2D NMs still face great challenges. The major barrier is their long-term safety, especially for substances that are not biodegradable in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…For example, theranostic platforms integrating collaborative chemotherapy, PTT, radiotherapy, and imaging diagnosis have been designed and verified to be useful for imaging diagnosis and enhanced tumor treatment. [ 158,159 ]…”
Section: Discussionmentioning
confidence: 99%
“…After treatment, the tumor inhibition rate of the experimental group reached nearly 78%, indicating the excellent anti-cancer effect of sonodynamic therapy based on 2D materials. In another study, 37 Chen et al used Au-modified BP nanosheets as sonodynamic agents for breast cancer therapy. They found that the sonodynamic performance of BP was significantly decreased after three sonications, indicating ultrasound-induced degradation of BP, as shown in Fig.…”
Section: External Stimulusmentioning
confidence: 99%
“…Moreover, the photosensitizing function and nontoxicity of BP result in an ideal platform for antitumor photothermal therapy (PTT) . Several reports are on the antitumor effects of BP-based drug delivery systems. However, these nanocarriers are primarily loaded with small-molecule drugs and nucleotides instead of bioactive macromolecules. In addition, polydopamine is most widely used for drug delivery applications, including photothermal and targeted therapies. Nevertheless, immunotherapy and PTT can synergistically inhibit tumor cells using multiple mechanisms, such as improving ferroptosis for synergistic photothermal-IDO immunotherapy. , …”
Section: Introductionmentioning
confidence: 99%